Caspase 4 Overexpression as a Prognostic Marker in Clear Cell Renal Cell Carcinoma: A Study Based on the Cancer Genome Atlas Data Mining - Meng, Lingfeng; Tian, Zijian; Long, Xingbo; Diao, Tongxiang; Hu, Maolin; Wang, Miao; Zhang, Wei; Zhang, Yaoguang; Wang, Jianye; He, Yuhui (Frontiers in Genetics, 2021)
The dysregulation of caspase 4 (CASP4) expression is related to the occurrence, development, and outcome of many malignant tumors; however, its role in clear cell renal cell carcinoma (ccRCC) remains unclear. Herein, we investigated the expression of CASP4 in tumor tissues and its relationship with clinical prognosis, immune infiltration, and drug sensitivity status of ccRCC patients. Oncomine and The Cancer Genome Atlas (TCGA) databases were used to determine CASP4 mRNA expression in ccRCC patients. The correlation between CASP4 expression and disease prognosis was evaluated using Kaplan–Meier analysis. Related pathways were obtained from TCGA database via gene set enrichment analysis (GSEA) and gene set variation analysis (GSVA). Meanwhile, genes co-expressing with CASP4 in ccRCC were investigated. Finally, we analyzed the proportion of tumor-infiltrating immune cells (TICs) using the CIBERSORT computational method and assessed CASP4 methylation and its relationship with drug sensitivity. Immunohistochemical analysis of 30 paired ccRCC and adjacent normal tissues confirmed the in silico results. CASP4 mRNA expression in ccRCC was significantly higher than that in the normal tissues, positively correlated with clinicopathological features (clinical stage and pathological grade), and negatively correlated with patient overall survival (OS). GSEA and GSVA showed that the genes in the CASP4-high expression group were primarily enriched in immune-related activities. Moreover, CIBERSORT analysis of TIC proportions revealed that activated CD4 memory T cells were positively correlated with CASP4 expression. Notably, methylation analysis revealed that the abnormal upregulation of CASP4 might be caused by hypomethylation. Finally, we found that the abnormal expression of CASP4 may be related to tumor drug resistance. Overall, our study shows that CASP4 is overexpressed in ccRCC and is an important factor affecting disease prognosis. Hence, CASP4 may serve as a potential prognostic biomarker and therapeutic target in ccRCC.